Perfusion-only imaging in pregnant women: A comparative reader study with implications for practice patterns. Issue 39 (30th September 2022) - Schroeder, Jennifer A.; Cao, Quy; Sotirchos, Vlasios S.; Gillman, Jennifer A.; Anderson, Thomas; Pilati, Stamatoula; Dubroff, Jacob G.; Farwell, Michael; Kozlov, Andrew; Korhonen, Katrina; Pryma, Daniel A.; Pantel, Austin R.
Abstract : This study seeks to understand the value of ventilation imaging in pregnant patients imaged for suspected pulmonary embolism (PE). Ventilation-perfusion (VQ) scans in this high-risk population were compared to ventilation-only scans. We hypothesize that in this relatively healthy population, the exclusion of ventilation scans will not impact the rate of scans interpreted as positive. This retrospective blinded comparative reader study on collated VQ scans performed on pregnant patients in the course of routine clinical care in a > 5 year period (03/2012 to 07/2017). Each set of VQ and perfusion only (Q) studies were reviewed by 8 readers (4 nuclear radiology fellows and 4 nuclear medicine faculty) in random order; the Q scans simply omitted the ventilation images. Readers recorded each study as PE, no PE, or non-diagnostic (prospective investigative study of acute PE diagnosis classifications). Logistic mixed effects models were used to test the association between scan type (VQ vs Q). 203 pairs of studies in 197 patients were included (6 patients had 2 scans). Subjects ranged from 14 to 45 years of age, with a median 28 years. A significant association between scan type and positive/negative classification. Q-scans received more positive classifications than VQ-scans (median of 7.6% vs 6.7%). No association was seen between scan type and positive/indeterminate classification, nor between scan type and negative/indeterminate classification. The exclusion of ventilation images in VQ-scans was associated with a higher rate of positive studies, but this difference was small (<1%). Given the overwhelmingly normal percentage of Q-exams (>90% in our study), and the benefits of omitting ventilation imaging, perfusion-only imaging should be considered a reasonable option for imaging the pregnant patient to exclude PE.